Measurement of combustion properties and ignition delay time of high performance alternative aviation fuels. (1st November 2021) - Han, Hee Sun; Sohn, Chae Hoon; Han, Jeongsik; Jeong, Byunghun
Graphical abstract: Highlights: Two alternative jet aviation fuels were manufactured for high performance. Combustion properties and ignition delay time were measured for fuel-feasibility test. The candidate fuels are mostly feasible for high performance and low emission. Blending of methylcyclohexane accelerates ignition at high temperature over 1, 050 K. Abstract: High-energy density aviation fuels are tested to see feasibility as alternative fuels to conventional jet fuels. They are derivatives of the existing high-energy density hydrocarbon fuels, exo -tetrahydrodicyclopentadiene and exo-tetrahydrotricyclopentadiene. Combustion properties and ignition delay times of these alternative fuels, called high performance fuels (HPF-1 and 2) are measured. Densities of HPF-1 and HPF-2 are similar to density of exo-tetrahydrodicyclopentadiene, but their H/C ratio, molecular weight, heat of combustion, derived cetane number, and threshold sooting index are quite higher than those of exo-tetrahydrodicyclopentadiene. It is found that HPF-1 and 2 have higher heat of combustion and lower sooting propensity than conventional jet aviation fuels when they are compared at the same fuel density. On the other hand, ignition delay time is measured in a temperature range from 950 K to 1, 300 K at 12 atm by using a shock tube. Results show that ignition delay time of the two fuels is shorter than exo-tetrahydrodicyclopentadiene. HPF-2 containing methylcyclohexane has much shorter ignition delay time than exo-tetrahydrodicyclopentadiene at high temperature over 1, 050 K.